Rasa Haus pada Pasien Gagal Jantung di Indonesia - Septa Meriana Lumbantoruan; Hsing-Mei Chen (Fakultas Keperawatan Universitas Andalas, 2021)
Thirst is a subjective symptom in patients with heart failure (HF) mostly was studied in the intensity dimension. However, the description of thirst at complete dimension in patients with HF is needed to be examined. This study aims to describe thirst in hospitalized patients with HF. A total of 85 patients with HF have completed questionnaires including demographics, disease-related factors, and thirst. Thirst was measure in thirst frequency (three items), thirst quality (seven items), thirst intensity (visual analog score 0-100 mm), and thirst distress (thirst distress scale in heart failure). This was a descriptive cross-sectional study. Thirst was reported every day and almost every day (71.7%), lasting for several hours (32.9%) and the thirstiest time was the whole day (47.1%). Thirst quality was described in discomfort (37.6%) and adverse events (31.8). Thirst intensity was in the mid-level and thirst distress have a mean of 24.72. Thirst was burdening on hospitalized patients with HF every day and make them feel distressed.Keywords: Heart failure; thirst